Effects of Temperament and Character Profiles on State and Trait Depression and Anxiety: A Prospective Study of a Japanese Youth Population. (22nd August 2012) - Lu, Xi; Chen, Zi; Cui, Xiaoyi; Uji, Masayo; Miyazaki, Wataru; Oda, Masako; Nagata, Toshiaki; Kitamura, Toshinori; Katoh, Takahiko
Abstract : Objective . To examine the effects of temperament and character profiles on state and trait depression and anxiety in a Japanese youth population. Method . Japanese university students were solicited for participation in a two-wave study, with assessments performed at Time 1 (T1) and Time 2 (T2), separated by a five-month interval. A total of 184 students completed the Japanese version of the temperament and character inventory (TCI) at T1 and the Hospital Anxiety and Depression Scale (HADS) at T1 and T2. We posited two latent variables, trait depression and anxiety, composed of the T1 and T2 HADS depression and anxiety scores, respectively. We also posited that temperament domain traits would predict character domain traits, and that all the personality traits would be linked to trait depression and anxiety and also predict T2 depression and anxiety. Results . Structural regression modeling showed that (1) only high Novelty Seeking predicted T2 Anxiety score, (2) trait depression and anxiety were linked to high harm avoidance and low self-directedness, and (3) trait depression was linked to high self-transcendence whereas trait anxiety was linked to low reward dependence, persistence, and cooperativeness. Conclusion . The characteristic associations between TCI subscales and depression and anxiety were limited to the trait rather than state aspects of depression and anxiety.